POLA ASUH ORANG TUA DALAM PERKEMBANGAN MORAL REMAJA (STUDI KASUS DI DESA PERNEK - Dian Supandi; Lukmanul Hakim; Roni Hartono (JURNAL PSIMAWA, 2019)
This study aims to describe parenting style in adolscent moral development (case study in the village of pernek). In this study the researchers made 3 parents from different families as research subjects and 3 (three) children from each research subject. The selection of the three subjects is based on different parenting methods used in the family. This study uses a descriptive qualitative approach. Data collection techniques using interviews, observation, and documentary. The results of this study indicate that parenting with authoritarian and permissive methods are more dominantly applied by subjects 1 and 2 where this upbringing can form a bad moral for children (adolescents). Then parenting with democratic methods is more dominant in subject 3 where this upbringing can form a good moral for children (adolescents). Authoritarian parenting has a low "acceptance" attitude but high control of adolescents, rigidity, physical punishment and high emotion. Permissive parenting has a high "acceptance" attitude but low control of adolescents and gives freedom to teens to express their encouragement or desires. Democratic parenting provides freedom and order, parents provide direction or inputs that are not binding on children, in this case parents are also objective to children, attention and also control of children's behavior so parents can adjust to their children's abilities.